2014
DOI: 10.1111/gcb.12606
|View full text |Cite
|
Sign up to set email alerts
|

Marine reserves help coastal ecosystems cope with extreme weather

Abstract: Natural ecosystems have experienced widespread degradation due to human activities. Consequently, enhancing resilience has become a primary objective for conservation. Nature reserves are a favored management tool, but we need clearer empirical tests of whether they can impart resilience. Catastrophic flooding in early 2011 impacted coastal ecosystems across eastern Australia. We demonstrate that marine reserves enhanced the capacity of coral reefs to withstand flood impacts. Reserve reefs resisted the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 64 publications
1
60
0
Order By: Relevance
“…Beyond temporal variability in community structure, coral reefs exemplify the expectation for reserve-driven cascades to increase resistance to and recovery from disturbance-specifically, increases in herbivore abundance and diversity in reserves, and therefore decreased macroalgae competition with corals, are expected to buffer coral response to disturbance (Bellwood et al 2004). However, observations of reserve effects on disturbance response in coral reefs vary: Increases in resistance (e.g., Olds et al 2014) and recovery rates (e.g., Mumby & Harborne 2010) occur in some cases, but meta-analyses indicate no average effect of reserves on resistance (Selig et al 2012) and slower rates of recovery on average in reserves compared with harvested areas (Graham et al 2011). In addition to dependence on complex, diffuse interactions, potential reasons for mixed resistance and recovery responses include dependence of recovery effects on reserve age (Selig & Bruno 2010), greater representation of stress-susceptible corals in more diverse systems (Graham et al 2011), and coupled responses across protected and harvested areas (as described for ecological resilience below).…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond temporal variability in community structure, coral reefs exemplify the expectation for reserve-driven cascades to increase resistance to and recovery from disturbance-specifically, increases in herbivore abundance and diversity in reserves, and therefore decreased macroalgae competition with corals, are expected to buffer coral response to disturbance (Bellwood et al 2004). However, observations of reserve effects on disturbance response in coral reefs vary: Increases in resistance (e.g., Olds et al 2014) and recovery rates (e.g., Mumby & Harborne 2010) occur in some cases, but meta-analyses indicate no average effect of reserves on resistance (Selig et al 2012) and slower rates of recovery on average in reserves compared with harvested areas (Graham et al 2011). In addition to dependence on complex, diffuse interactions, potential reasons for mixed resistance and recovery responses include dependence of recovery effects on reserve age (Selig & Bruno 2010), greater representation of stress-susceptible corals in more diverse systems (Graham et al 2011), and coupled responses across protected and harvested areas (as described for ecological resilience below).…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 99%
“…The mechanisms that can, theoretically, lead to alternative stable states range from size-dependent or stage-dependent predator-prey interactions in temperate systems (e.g., Baskett et al 2006; see Section 3.1) to macroalgal inhibition of coral recruitment and dilution of grazing in tropical reefs (e.g., Mumby et al 2007). Therefore, in temperate reefs, observed increases in predator size and biomass in reserves might increase the resilience of kelp forests to shifts to urchin barrens (e.g., Ling et al 2009), and in tropical reefs, observed increases in herbivores in reserves might increase the resilience of coral-dominated states to shifts to macroalgal-dominated states (e.g., Olds et al 2014). However, direct empirical tests remain elusive.…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 99%
“…In general, proposed adaptation actions are designed either to build resilience to climate change through the management of existing threats, strengthening of protected area networks or ecosystem restoration, or are otherwise designed to address specific issues associated with exposure and sensitivity to climate change through 'hard' or ecological engineering actions Lukasiewicz et al 2013Lukasiewicz et al , 2016. Although there are limits to what protected-area design can achieve in terms of climate-change adaptation, enhancing protected-area management can help reduce non-climatic stresses and increase resilience of the ecosystem, as well as enabling efficient adaptive management (Pittock et al 2008, Olds et al 2014. 'Soft' adaptation measures that promote cultural and institutional change, for example, education, are also likely to be essential for effective adaptation to climate change.…”
Section: Adapting Wetland Managementmentioning
confidence: 99%
“…However, it is not all bad news. As we are increasingly understanding the many facets of habitat-species interactions (Thomsen et al 2010) we also find ways to minimise impacts through less destructive harvesting (Stagnol et al 2016) and habitat protection (Olds et al 2014), as well as new management procedures (Shiel and Howard-Williams 2016), and we discover new opportunities for ecological engineering, reclaiming and maximising the ecological value of man-made structures increasingly encroaching on our coastlines (e.g. Evans et al 2016;Firth et al 2016).…”
Section: Introductionmentioning
confidence: 99%